Electromagnetic Compatibility Analysis of Power Electronic Traction Transformer - YANG Deyong; YANG Tianfan; ZHU Bingquan; ZHI Yongjian (Kongzhi Yu Xinxi Jishu)
Power electronic traction transformer has the characteristics of high voltage, high switching frequency, high power density and high system integration. Electromagnetic interference of semiconductor device switch action to the sensitive control circuit becomes key factor for the reliability of system. According to the characteristics of high voltage cascaded system of PETT, a near-field coupling model based on distributed parameters was proposed to analyze the influence of switch action of main circuit IGBT on the sensitive control circuit. Combining with the simulation model, key factors influencing electromagnetic interference were analyzed.